2021
DOI: 10.3390/foods10112887
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Krill Lipid Fractions Differentially Reduce LPS-Induced Inflammatory Markers in RAW264.7 Macrophages In Vitro

Abstract: Antarctic krill oil is an emerging marine lipid and expected to be a potential functional food due to its diverse nutrients, such as eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), phospholipids, astaxanthin and tocopherols. Although krill oil has been previously proved to have anti-inflammatory activity, there is little information about the relationship between its chemical compositions and anti-inflammatory activity. In this study, the RAW264.7 macrophages model was used to elucidate and compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Macrophages are important immune cells, which participate in the modulation of a series of inflammations and autoimmune diseases through either specific (cellular immunity) or non-specific defenses (innate immunity) in vivo ( 58 ). Inflammatory responses induced by LPS in macrophages have been commonly used as a classical model to evaluate the anti-inflammatory activity of active substances ( 20 22 , 59 ). Macrophages can be polarized into classically activated macrophages (M1) and alternatively activated macrophages (M2) in the immune system, performing pro-inflammatory and anti-inflammatory functions, respectively ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages are important immune cells, which participate in the modulation of a series of inflammations and autoimmune diseases through either specific (cellular immunity) or non-specific defenses (innate immunity) in vivo ( 58 ). Inflammatory responses induced by LPS in macrophages have been commonly used as a classical model to evaluate the anti-inflammatory activity of active substances ( 20 22 , 59 ). Macrophages can be polarized into classically activated macrophages (M1) and alternatively activated macrophages (M2) in the immune system, performing pro-inflammatory and anti-inflammatory functions, respectively ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depressive-like behaviors in animals could be induced by cytokines or cytokine inducers such as lipopolysaccharide (LPS) administration or chronic mild stress (16)(17)(18)(19). In the relevant researches, LPS was commonly employed to induce inflammatory responses in macrophages, which was used as a classical model to evaluate the anti-inflammatory activity of active substances (20)(21)(22). On the other hand, anti-inflammatory agents were used to suppress pro-inflammatory cytokine level in both humans and animals (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, DHA and EPA inhibited arachidonic acid metabolism and decreased the expression of the gene coding for COX-2. 115,116 In turn, curcumin acts by intermolecular interactions through van del Waals forces that inhibit the activity of COX-1 and COX-2. 117 Ma et al 118 studied the combined effects of fish oil and curcumin, and reported that the combination of ω-3 PUFA and curcumin significantly prevented cognitive decline in 3xTg-AD mice evaluated through the Y-maze test.…”
Section: Anti-aβ Activitymentioning
confidence: 99%
“…This is how COX, lipoxygenase (LOX), and cytochrome P450 act as substrates. In this regard, DHA and EPA inhibited arachidonic acid metabolism and decreased the expression of the gene coding for COX‐2 115,116 . In turn, curcumin acts by intermolecular interactions through van del Waals forces that inhibit the activity of COX‐1 and COX‐2 117 …”
Section: Bioactive Compounds With Potential Biological Activity In Admentioning
confidence: 99%
“…Omega-3 polyunsaturated fatty acids play an important role in human physiology; therefore, they are widely used as health supplements [ 1 , 2 , 3 ]. Recently, krill oil extracted from Antarctic krill ( Euphausia Superba ) has attracted attention as a source of long-chain omega-3 fatty acids, eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) [ 4 ]. Unlike in other marine fish oils, most EPA and DHA of krill oil exist in the form of phospholipids (PLs) rather than in the form of triglycerides (TGAs) [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%